Knowledge Sharing sebagai Upaya Peningkatan Kompetensi dan Kinerja Pegawai (Studi pada Pusat Pelatihan dan Pengembangan dan Pemetaaan Kompetensi Aparatur Sipil Negara Lembaga Administrasi Negara) - Nugroho, Candra Setya (Jurnal Ilmiah Administrasi Publik, 2020)
Knowledge is a strategic asset of an organization which is still largely in the minds of its employees. Therefore the organization needs to make special efforts to catch it. The PKASN LAN Puslatbang LAN attempts to capture this knowledge through knowledge sharing among its employees. Knowledge sharing aims to improve the knowledge and performance of employees. This research aims to find out various knowledge sharing methods applied by PKASN LAN Puslatbang, knowing the supporting factors of implementing knowledge sharing, and knowing the inhibiting factors. The research method that will be used is descriptive qualitative method. Based on the research that has been done, it is obtained that the knowledge sharing in the PKASN Puslatbang is carried out through employee meeting methods, inhouse training, discussions between employees, and other methods. Supporting factors are organizational culture, human resources, and leadership support. The inhibiting factors are institutional, governance, and the absence of rewards for employees who share their knowledge.